2023
DOI: 10.18203/2349-2902.isj20231745
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of wandering spleen with its unreported associations: case report and literature review

Asha R. Digumarthi,
Seema Khanna,
Satendra Kumar
et al.

Abstract: Wandering spleen (WS) is a rare clinical entity with unclear clinical picture. Patient can be asymptomatic or can present with acute abdomen, based on the degree of associated splenic torsion, but most of the cases needed an emergency splenectomy. We herein report an unusual presentation of a wandering spleen in the elderly with thrombocytosis, portal, and splenic vein thrombosis, and sinistral hypertension. To the best of our knowledge, this is the first case report documenting all these associations altogeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It predisposes to splenic torsion and SVT, leading to SVH. 39 A review of 20 case reports found that GI bleeding was the most common chief complaint (45%), followed by abdominal pain (40%). Gastric varices were observed in 90% of the patients, 30% had splenic varices, and no esophageal varices were present.…”
Section: Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…It predisposes to splenic torsion and SVT, leading to SVH. 39 A review of 20 case reports found that GI bleeding was the most common chief complaint (45%), followed by abdominal pain (40%). Gastric varices were observed in 90% of the patients, 30% had splenic varices, and no esophageal varices were present.…”
Section: Inflammationmentioning
confidence: 99%
“…Several case reports have also been published (Tables 1D and 2D). 39,41 Essential thrombocythemia: Essential thrombocythemia is a myeloproliferative neoplasm characterized by JAK/STAT pathway activation, leading to elevated platelet levels with an increased risk of thrombosis, including in the SV with consequent SVH. The estimated prevalence of SVT is 4% to 13%.…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation